Description of Development in Andalusian Poetry "The Palaces of the Kings of the Taifas" Artistic Study - Alatawi, Mutair Eid Mohammed (Journal of Arabic Language Sciences and Literature, 2023)
The current study aimed at explaining Development in Andalusian poetry, the palaces of its kings, and the nature of life in the period of The Palaces of the Kings of the Taifas, as well as poetry about palaces after the decline and fall of states, and then the impact of palaces in literary life. The researcher relied on several approaches in this study, including the descriptive analytical and deductive approach, the historical approach. The study in its general framework consists of an introduction, a preface, three chapters a conclusion, then the conclusion and the results of the research, and indexes. After reviewing the core issues the research resulted in a number of results, including: that the fall of the Umayyad Caliphate in Andalusia was the beginning of civil wars due to ethnic and national conflicts between Arabs and Berbers that contributed to the rupture of the unity of Andalusia.This resulted in the emergence of several states in Andalusia known as “the Taifas” states. And the time of the Taifas kings began from the year (422-487 AH, 1029-1092) in Andalusia and these states inherited the place of the caliphate, and the name “ the Taifas” became clear in describing the country which was distributed by several kingdoms, and hose states were divided into three categories: Arabs, Berbers, and loyalists, and this division was according to the families that ruled them and their ethnic affiliation. The system of government in most cases was tyranny, dictatorship and fighting, because every ruler made himself a king and an authority, and he was called the "Commander of the believers". The period of the " Kings of the Taifas " was characterized by social disintegration and political weakness, but it was a time of civilized progress and cultural advancement, and the atmosphere created a suitable place for writers and poets, and the literary movement was very active, where Andalusians contributed to spreading the common Arab heritage, period of the " Kings of the Taifas " was also considered as one of the most prominent period of literature flourishing. And thought in Andalusia, where Arabic literature flourished in this period was unparalleled in other period that preceded it.